Sex-Related Differences in the Severity of Neonatal Opioid Withdrawal Syndrome: A Single-Center, Retrospective Cohort Study - Anderson, Victoria A.; Anbalagan, Saminathan; Favara, Michael T.; Stark, Daniela; Carola, David; Solarin, Kolawole O.; Adeniyi-Jones, Susan; Aghai, Zubair H. (American Journal of Perinatology, 2024)
Objective Factors associated with the development and expression of Neonatal Opioid Withdrawal Syndrome (NOWS) are poorly understood. There are conflicting data on the role of infant sex in NOWS. Some studies have suggested that infant sex predicts NOWS severity and adverse outcomes, with male infants being more vulnerable. This study aimed to analyze if infant sex is associated with the severity of NOWS among those who require pharmacologic treatment.Study Design This is a retrospective cohort study of term and late-preterm infants (≥35 weeks gestation) exposed to in utero opioids, born between September 2006 and August 2022, and required pharmacologic treatment for NOWS. Maternal and infant demographics were collected. Indicators of the severity of NOWS (duration of medical treatment (DOT), duration of hospitalization, maximum dose of opioid treatment, and use of secondary medications) were compared between male and female infants. Standard statistical tests and regression analysis were used to establish the differences in outcomes after accounting for confounders and baseline differences.Results Out of the 1,074 infants included in the study, 47.9% were female, and 52.1% were male. There was no significant difference in demographic and baseline clinical characteristics between groups except for anthropometry (birth weight, head circumference, and length) and Apgar score at 5 minutes. The median DOT (25 days [14, 39] vs. 23 days [13, 39], p = 0.57), length of hospital stay (31.5 days [20, 44] vs. 28 days [20, 44], p = 0.35), treatment with phenobarbital (24.7 vs. 26.3%, p = 0.56), and clonidine (3.9 vs. 3.8%, p = 0.9) were similar in both groups. The differences remained nonsignificant after adjusting for birth anthropometric measurements, gestational age, 5-minute Apgar score, small for gestational age status, and maternal exposure to benzodiazepines.Conclusion In this cohort of neonates, sex-related differences were not identified to influence the severity of NOWS among those who required pharmacological treatment.Key Points
Keywords: NOWS; sex; gender; neonate; NAS; risk factors